2022
DOI: 10.3390/ijerph19084882
|View full text |Cite
|
Sign up to set email alerts
|

Translation, Cross-Cultural Adaptation, and Validation of the Malay-Version of the Factors Influencing Community Willingness to Perform Cardiopulmonary Resuscitation and Use an Automated External Defibrillator Questionnaire

Abstract: Limited factors influence community willingness to perform cardiopulmonary resuscitation and use an automated external defibrillator, making it difficult to take preventive and control measures to improve the survival of patients with out-of-hospital cardiac arrest. In this study, we translated and evaluated the Malay-language version of the cardiopulmonary resuscitation and an automated external defibrillator questionnaire. The translation and evaluation involved three phases: development, translation and cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The difficulty of the KOR-AED items varied, with certain items showing a medium level of difficulty, especially the questions related to the use of the AED and others a higher discriminatory index, In addition, Cronbach's alpha of 0.75 indicates an acceptable internal consistency of the KOR-AED test, however other studies of development and validation of questionnaires in CPR and AED use showed a Cronbach's alpha of 0.84 (11) and 0.9 (12) attributable to social contexts and familiarity with the use of the AED other than our own.…”
Section: Discussionmentioning
confidence: 97%
“…The difficulty of the KOR-AED items varied, with certain items showing a medium level of difficulty, especially the questions related to the use of the AED and others a higher discriminatory index, In addition, Cronbach's alpha of 0.75 indicates an acceptable internal consistency of the KOR-AED test, however other studies of development and validation of questionnaires in CPR and AED use showed a Cronbach's alpha of 0.84 (11) and 0.9 (12) attributable to social contexts and familiarity with the use of the AED other than our own.…”
Section: Discussionmentioning
confidence: 97%
“…[4]. Therefore, most often, witnesses of OHCA are bystanders without medical education and with very varying degrees of training in resuscitation [8,9]. The survival rate and good neurological outcome of OHCA victims are in uenced by early diagnosis, alerting the emergency medical services (EMS) system, providing high-quality resuscitation by a bystander, and the use of an automatic external de brillator (AED) as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding of the factors that drive community willingness to learn and perform CPR, for instance, are limited, and no universal instrument has been validated to assess such variables of in uence. 23 The success of our implementation of community CPR and bleeding control skills despite this uncertainty was likely impacted by the efforts of the community liaisons, who a) assured their respective community members would want to learn to the skills of bystander CPR and bleeding control; b) coordinated with the health system in regards to planning the event and c) con rmed community members arrived and participated on the date of training.…”
Section: Discussionmentioning
confidence: 99%